Dynamic Young's Modulus, Morphological, And Thermal Stability Of 5 Tropical Light Hardwoods Modified By Benzene Diazonium Salt Treatment - Islam, M.S.; Rahman, M.R.; Jusoh, Ismail; Ahmed, Abu Saleh; Idrus, Mun'aim; Hamdan, Sinin (BioResources, 2011)
In this study the tropical light hardwood species jelutong (Dyera costufata), terbulan (Endospermum diadenum) , batai (Paraserianthes mofuccana), rubberwood (Hevea brasiliensis), and pulai (Alstonia pneumatophora) were treated with benzene diazonium salt to improve their dynamic Young's modulus (Ed), and thermal stability. Benzine diazonium salt reacted with cellulose in wood and produced 2,6 diazocellulose by a coupling reaction, as confirmed by Fourier transform infrared (FTIR) spectroscopy. Values of Ed were calculated from the free free flexural vibration method and found to increase on treatment. The morphological properties were studied by FTIR and scanning electron microscopy (SEM) and found to be changed. Thermal properties of treated wood samples were evaluated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The treated wood samples exhibited an increased thermal stability relative to the untreated wood samples; this increase may be related to the formation of 2, 6 diazo cellulose compound.